Ketahanan Perusahaan di Era Ketidakpastian Global: Analisis Dampak Karakteristik Audit terhadap Ketepatan Waktu Pelaporan Keuangan - Lintang Kurniawati; Annisa Fitriana Kusumawati; Haryo Bhaskoro; Rafi Amani Muflih Rahardi; Putri Dilla Maliana; Pinnacle Ferdyamin; Ahmad Syihan Setiawan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Global uncertainty triggered by the COVID-19 pandemic has caused significant disruptions to economic stability, particularly within vital sectors such as infrastructure, utilities, and transportation. Data indicate that these sectors experienced substantial revenue declines—87.9%, 90.90%, and 90.34%, respectively. These sharp decreases not only highlight the vulnerability of business sectors to external shocks but also underscore the importance of corporate resilience in responding to crises. Under such high-pressure circumstances, access to external financing becomes crucial for maintaining company operations. However, investors’ decisions to provide capital largely depend on the quality and credibility of the financial information disclosed by companies. Audited financial statements serve as a primary instrument for building investor trust, as they reflect managerial transparency and accountability. Furthermore, in this context, auditing plays a vital role in ensuring the credibility of financial information and the timeliness of financial reporting, which reflects a company’s responsiveness and accountability in maintaining resilience. This study aims to: (1) analyze the relationship between audit characteristics and the timeliness of financial reporting, and (2) provide empirical evidence regarding the impact of timely audited reporting on corporate resilience during periods of global uncertainty. A quantitative research method was employed, utilizing financial statement data from companies in the infrastructure, utilities, and transportation sectors for the years 2020 to 2023. The data were processed using SPSS 26. The findings reveal that auditor reputation has a significant effect on financial reporting timeliness. Meanwhile, audit location, auditor rotation, and audit fees were found to have no significant effect. Furthermore, timely financial reporting is proven to be a key factor in helping companies navigate economic uncertainty and maintain resilience amid ongoing global disruptions.